Microstructure and mechanical properties of Pb-4%Sb alloy processed by equal channel angular pressing - Roberto Braga Figueiredo; André Luiz de Moraes Costa; Margareth Spangler Andrade; Maria Teresa Paulino Aguilar; Paulo Roberto Cetlin (Materials Research, 2006)
Equal Channel Angular Pressing (ECAP) is the most prominent SPD (Severe Plastic Deformation) method for the production of ultrafine and nanostructured metals, and has been extensively employed and analyzed. This technique was applied to a Pb-4%Sb alloy at room temperature, in order to study its effect on a low melting point and multiphase metallic material. The material was subjected to effective strains higher than 9, after 8 passes of processing, where dynamic and static recrystallization are expected during and after each pass. This eliminates any grain refinement and allows the analysis only of the microstructural effects associated with second phase redistribution and eventual precipitate dissolution. ECAP followed route C, which eliminates structural alignment after each even ECAP pass, facilitating the study of the microstructural evolution. It is shown that three ECAP passes are necessary to completely break the lamellar structure of the as cast strucure and that antimony dissolves into the lead rich matrix. Dynamic recrystallization and structural changes reduce the material strength and change the flow curve format.